Eksplorasi Etnomatematika Arsitektur Masjid Agung Nurul Kalam Islam: Bagaimana Kaitannya dengan Nilai-Nilai Islam - Nalim; Fahmy, Ahmad Faridh Ricky; Shinta, Dewi; Albab, Ulul; Ramadhan, Muna Zahro (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
This research aims to explore ethnomathematics in the architecture of the Nurul Kalam Grand Mosque in Pemalang and its relation to Islamic values. This qualitative research collects data through interviews, observation and documentation studies. The research results show that (1) there is an exploration of the architecture of the Nurul Kalam Pemalang grand mosque which can be seen from the planning design concept showing the spatial layout, symbols, motifs and forms of buildings typical of Pemalang. (2) the content of Islamic religious education values is attached to the philosophical meaning in every corner, the shape of the building and various ornaments in the mosque such as a pyramid-shaped roof with straight line ornaments as a representation of the faith, also a tower with a height of 51 meter as a symbol of the nature of Allah's compassion found in Asmaul Husna. (3) the implementation of Islamic education is found in the main function of the mosque as a place of worship and a scientific center. This is realized through various activities such as places to study the Qur’an, regular recitations, libraries and social activities during Ramadan. The contribution of this research can be used as a reference for Islamic education to increase scientific knowledge through mosque architecture for broad-minded Islamic education.